PENUMBUHAN KETERAMPILAN TERPADU BERBAHASA INGGRIS MAHASISWA PESERTA MKDU BAHASA INGGRIS - Gunawan Gunawan (Universitas Negeri Yogyakarta, 2003)
Abstract This study is trying to optimize the effectiveness of English lecturers held in the non-English departments conducted by lecturers from the English Department of the Faculty of languages and Art (FBS) of the State University of Yogyakarta (UNY). To achieve the objective, this study sets the methods as: 1) selecting core material,2) developing activities in the lecturing, 3) training the candidate lecturers 4) implementing the designed instruction, 5)evaluating and discussing the results of the implementation of the instruction in the target classes. The learning processes run well in the seven target classes, but it runs so slowly in one target class because on belief conflict in the lecturer’s side. Positive aspects reported are: 1) the teaching method is practical, 2) easy to follow, 3) giving new experience and spirit to students; 4) continually given homework are promoting strong students’ motivation and spirit to study harder, 5) the exercises are helping students to have better understanding and competence of English; teaching materials, methods, and techniques are very effective; the teaching learning processes are felt very special, new, enjoyable, and promoting students’ competencies of English. Negative aspects reported are materials to learn are too much comparing to time available, too much of memorization, using uncommon terms, too much time used for discussing formulas, too much demanding of command on teaching materials and methods to the teachers, too many numbers of formative tests, short of rich examples for each type of sentences, lack intention of promoting oral communication. Keywords: lecturing of English, basic general subject, the non-English department, learning instruction design.